Pengembangan Produk Eco print untuk Diversifikasi Kerajinan Tangan pada UMKM Duta Craft Mojoroto, Kediri. - Wahyuni, Adhitya Tri; Ghoza, Bhalda Arija; Dwi A, Mochammad Hendrico; Wulandari, Nelly Rizka Tri; Nizam, Moh Zain Syahrun; Wulandari, Rahmawati (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to support Duta Craft MSMEs in Mojoroto, Kediri, in developing eco-print products as a form of handicraft diversification. The main objective of this activity is to increase creativity and product competitiveness through sustainability-based innovation. The method used is Participatory Action Research (PAR), which involves MSMEs in every stage, from technical training, production, to marketing. The training includes an introduction to eco-print techniques, the use of natural materials, and digital marketing strategies. The results of the community service show an increase in participants' knowledge and skills in eco-print techniques. The innovative products have succeeded in attracting the attention of new consumers, increasing their selling value, and opening up opportunities for market diversification. Thus, this activity has a positive impact on product development, business sustainability, and increasing the income of Duta Craft MSMEs.